The Work-Related Stress and Well-Being of Teachers-An Exploratory Study within Primary Schools in Italy - Giulia Arbia; Agostino Carbone; Irene Stanzione; Giordana Szpunar (MDPI AG, 2023)
This study analyzes the critical aspects of the professional life of primary school teachers in a southern European context. The social changes of the last two decades have profoundly impacted teachers' well-being, putting a strain on their ability to adapt to sometimes unfair working conditions. For this purpose, we interviewed twenty teachers (M = 38.85; DS = 9.17) from different areas of Italy and analyzed data using the grounded theory method. Through a data analysis, we summarized and emphasized eight core themes. The results show the effects of the gradual impoverishment of the recognition for the role of the teacher, highlighting the difficulty for teachers in renegotiating more flexible workload assessments and reinforcing psycho-emotional skills for developing a teaching methodology that is attentive to the psycho-emotional needs of their pupils. Schools emerge as a rigid working context where a competent organizational function is often absent. The practical psychological implications of this are discussed.